Perception of Teachers in the use of Electronic Platforms to Support Face-to-Face Teaching During the term of The State of Emergency due to Covid-19: Case of the Pedagogical University of Maputo - Constantino Zunguze, Manuel; Zildo António Tsambe, Malaquias (RENOTE, 2021)
COVID-19 pandemic forced most of the high education institutions to revert their teaching and learning process from face-to-face teaching system to the process of teaching and learning through the use of electronic platforms. Due to this situation, each high education institution has defined one or a set of electronic platforms to continue to guarantee the effectiveness of teaching classes during this period. It was from the above that this research was developed, which aimed to analyze the perception of teachers at the Pedagogical University of Maputo about accessibility and the use of electronic platforms as a resource to support face-to-face teaching during the term of COVID-19 pandemic. The results showed that most of the teachers interact with the students via WhatsApp and Email through their mobile devices and laptops.